Impact of fatigue in Crohn's disease is negatively related to resting state functional connectivity between the superior parietal lobule and parahippocampal gyrus/hippocampus - McIver, Theresa A.; Bernstein, Charles N.; Marrie, Ruth Ann; Figley, Chase R.; Uddin, Md Nasir; Fisk, John D.; Graff, Lesley A.; Patel, Ronak; Mazerolle, Erin L.; Kornelsen, Jennifer (Frontiers in Human Neuroscience, 2025)
IntroductionCrohn's disease is one phenotype of inflammatory bowel disease (IBD). Fatigue is a common and burdensome symptom for persons with Crohn's disease. Despite its detrimental impact on health-related quality of life, the pathophysiology of fatigue in Crohn's disease is not fully understood. Specifically, basic research on the difference in brain functioning associated with fatigue in Crohn's disease is scarce. This study aimed to address this knowledge gap by identifying fatigue-related differences in brain resting state functional connectivity. in Crohn's disease.MethodsParticipants included 49 adults with Crohn's Disease (Mage 53 yrs, 35 females) and 49 healthy controls (Mage 50 yrs, 31 females). The Fatigue Impact Scale (FIS) assessed impact of fatigue across three domains (physical, cognitive, and psychosocial) as well as total impact of fatigue. The Harvey-Bradshaw Inventory (HBI) assessed disease activity. Magnetic Resonance Imaging of brain functional connectivity during resting state (i.e.,: wakeful rest) was assessed in relation to scores on the FIS (total and for each domain). Moderation analyses tested whether brain resting state functional connectivity moderates the relationship between disease activity and fatigue.ResultsThe Crohn's disease group reported more severe fatigue than the healthy control group in each domain of the FIS. For the Crohn's disease group, increasing fatigue was associated with decreasing synchronicity of brain function (i.e., functional connectivity) between the superior parietal lobule and the parahippocampal gyrus/hippocampus. Unlike in the healthy control group, an increasing impact of physical fatigue was associated with decreasing functional connectivity between these ROIs for the Crohn's disease group (TFCE = 16.88, p-FDR = 0.03). Moderation analyses revealed a significant interaction between disease activity, total fatigue, and functional connectivity of the right superior parietal lobule and left anterior parahippocampal gyrus (ΔR2 = 0.058, F = 5.445, p = 0.0245). Higher scores on the HBI were only associated with higher total scores on the FIS in persons with Crohn's disease who exhibited negative functional connectivity between these brain regions.DiscussionIn people with Crohn's disease, fatigue increases as functional connectivity between brain regions involved in sensorimotor integration and memory processing decreases.